2017
DOI: 10.1158/1538-7445.am2017-5457
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5457: OGT restrains the NRF2 antioxidant pathway via O-GlcNAcylation of KEAP1

Abstract: O-GlcNAcylation is a reversible post-translational modification that adds an O-linked β-N-acetylglucosamine (O-GlcNAc) moiety onto serine/threonine residues of target proteins. This modification is regulated by only two enzymes: O-GlcNAc transferase (OGT, the writer) and O-GlcNAcase (OGA, the eraser) in mammals. Recent studies have revealed that OGT expression and O-GlcNAc modifications are elevated in several cancers, but specific O-GlcNAc targets are not well defined. We conducted a global transcriptome prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Meanwhile, the protein KEAP1 has also garnered the interest of numerous researchers, with prior evidence demonstrating that its O-GlcNAcylation S104 can effectively cause ubiquitination and degradation of NRF2 (Chen et al, 2017b), which thus corroborates our findings. Moreover, (Chen et al, 2017a) identified a positive correlation between lowered OGT activity and NRF2 activation in several gene expression datasets of human tumors, while NRF2 in turn has been found to be activated in response to oxidative stress and repressed by KEAP1. Furthermore, the in vitro findings of our study were also validated by in vivo experimentation, which highlighted that OGT repressed autophagy through the KEAP1/NRF2 axis and accelerated high phosphateinduced VC in 5/6 Nx rats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Meanwhile, the protein KEAP1 has also garnered the interest of numerous researchers, with prior evidence demonstrating that its O-GlcNAcylation S104 can effectively cause ubiquitination and degradation of NRF2 (Chen et al, 2017b), which thus corroborates our findings. Moreover, (Chen et al, 2017a) identified a positive correlation between lowered OGT activity and NRF2 activation in several gene expression datasets of human tumors, while NRF2 in turn has been found to be activated in response to oxidative stress and repressed by KEAP1. Furthermore, the in vitro findings of our study were also validated by in vivo experimentation, which highlighted that OGT repressed autophagy through the KEAP1/NRF2 axis and accelerated high phosphateinduced VC in 5/6 Nx rats.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have evidenced the promotive effects of OGT and KEAP1 in vascular damage, wherein the transcription factor NRF2 was found to restrict VC (Ha et al, 2014;Zhang et al, 2019). OGT induces O-glycosylation of KEAP1 at serine 104 (S104) and then facilitates ubiquitination and degradation of NRF2 (Chen et al, 2017a). Subsequently, our efforts were aimed at further validating their functions in VSMCs.…”
Section: Ogt Overexpression Accelerates Keap1 Glycosylation Leading Tmentioning
confidence: 99%